Peningkatan Hasil Belajar Siswa dengan Proyek Pembuatan Poster Tentang Norma Pada Siswa Kelas VII A - Heriyanto, Danur (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This research is entitled "Improving Student Learning Outcomes with the Poster Making Project on Norms". The subjects of this study were all class VII A students at SMP Muhammadiyah 3 Karangpandan for the 2022/2023 academic year. The purposes of this study were: (1) To find out the learning outcomes of class VII A students at SMP Muhammadiyah 3 Karangpandan before learning was carried out with the poster-making project, (2) To find out how the poster-making project could improve student learning outcomes for class VII A students at SMP Muhammadiyah 3 Karangpandan, and (3) to find out the results of increasing student learning outcomes in class VII A SMP Muhammadiyah 3 Karangpandan after learning by making a poster making project on the subject matter of Norma. Based on the aspects to be achieved, the Classroom Action Research (CAR) method was used in this study because in general CAR is very suitable for improving the quality of research subjects. Based on the results of the research, it was found that the poster making project could improve student learning outcomes on the subject of Norms